Pengaruh Kualitas Audit dan Corporate Governance terhadap Integritas Laporan Keuangan pada perbankan di BEI 2019-2023 - Mulyani, Rina; Sopian, Dani (Journal of Information System, Applied, Management, Accounting and Research, 2025)
This study examines how audit quality and corporate governance affect the integrity of financial statements in banking companies listed on the Indonesia Stock Exchange (IDX) 2019 - 2023. Financial statements are the main communication tool between companies and stakeholders, so their integrity is very important for transparency and accountability. This study conducted multiple linear regression analysis on secondary data from the annual financial statements of 19 of 30 banking organizations selected using purposive selection. The results showed that independent boards of commissioners, audit committees and audit quality affect the reliability of financial statements. These findings highlight the shortcomings of corporate governance in the banking sector and the need to reform governance institutions to provide more open and credible financial disclosures. This study is expected to improve corporate governance in the banking sector and the honesty of financial statements.